THE CONCEPTS OF UNITY IN ISLAM IN KH. WAHAB HASBULLAH'S THOUGHT - Syamsuddini, M. Najich; M. Zainuddin, M. Zainuddin; Soleh, Achmad Khudori (State Islamic University North Sumatra, 2023)
Abstract: The concept of unity needs to be studied on the basis of Islamic pretexts, describing the unity of Muslims in order to organize the continuity of life. The purpose of this study is to offer the concept of unity according to KH. A Wahab chasbullah so as to provide an understanding of the reader in responding to divisions within the Muslim community, both on a national and international scale. This research took the form of library research , in which several articles were found in the media, especially the NU swara magazine, from 1920-1930. The results of this study have found that KH. A Wahab chasbullah about unity based on QSAli imron verse 103, QS Al-hujurat verse 13, several hadiths and qoul sohabi . According to him, the importance of the unity of the Islamic Ummah is that the purpose of Islam for humanity can be achieved, social order with the understanding of Islam rahmatan lilalamin is able to bridge national and international scale relations. Further research can be developed for researchers by focusing on KH. A Wahab chasbullah in terms of education, politics, or the NU organizational movement in his day.Keywords: Thought KH. A Wahab chasbullah, the concept of unity, Muslims